Joint learning in innovative R&D collaboration - Bäck, Iivari; Kohtamäki, Marko (Taylor & Francis, 2016)
The present study analyzes the mechanisms and facilitators behind joint learning in R&D collaborations by way of a qualitative comparative case study analyzing three supplier relationships and three internal R&D partnerships of the focal organization. The results suggest a single joint learning process for internal and external relationships in which the role of the customer and the facilitation of the joint learning process vary depending on the context. Whereas the role of motivation is central for joint learning in the internal relationships, mutual trust is important to the external relationships.
Keywords: Joint learning; R&D; collaboration; innovation; innovations; fi=Strateginen johtaminen|en=Strategic Management|